2003
DOI: 10.1046/j.1460-9568.2003.02607.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid mechanism in reinstatement of heroin‐seeking after a long period of abstinence in rats

Abstract: Because opioid and cannabinoid systems have been reported to interact in the modulation of addictive behaviour, this study was aimed at investigating the ability of cannabinoid agents to reinstate or prevent heroin-seeking behaviour after a prolonged period of extinction. In rats previously trained to self-administer heroin intravenously, non-contingent non-reinforced priming administrations of heroin and cannabinoids were presented after long-term extinction, and lever pressing following injections was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 19 publications
6
92
2
Order By: Relevance
“…This apparent discrepancy may result from a combination of different procedural factors. First, in previous studies, daily access time to heroin was longer than the minimum of the present study (ie, 1 h) and ranged between 2 and 12 h, with 3 h being the most frequent duration of access (eg, de Wit and Stewart, 1981;Stewart and Wise, 1992;Shaham and Stewart, 1995;De Vries et al, 1998;Fuchs and See, 2002;Fattore et al, 2003;Leri et al, 2004;Luo et al, 2004;Yao et al, 2005). Thus, together with the present findings, this difference may point to the existence of some threshold duration below which most individuals readily learn to take heroin without becoming responsive to its priming effects and above which they begin to respond to these effects.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This apparent discrepancy may result from a combination of different procedural factors. First, in previous studies, daily access time to heroin was longer than the minimum of the present study (ie, 1 h) and ranged between 2 and 12 h, with 3 h being the most frequent duration of access (eg, de Wit and Stewart, 1981;Stewart and Wise, 1992;Shaham and Stewart, 1995;De Vries et al, 1998;Fuchs and See, 2002;Fattore et al, 2003;Leri et al, 2004;Luo et al, 2004;Yao et al, 2005). Thus, together with the present findings, this difference may point to the existence of some threshold duration below which most individuals readily learn to take heroin without becoming responsive to its priming effects and above which they begin to respond to these effects.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, together with the present findings, this difference may point to the existence of some threshold duration below which most individuals readily learn to take heroin without becoming responsive to its priming effects and above which they begin to respond to these effects. Second, in most, except a few, previous studies, responding during reinstatement testing was followed by discrete stimuli that were originally paired with heroin injections (eg, de Wit and Stewart, 1981;Stewart and Wise, 1992;Shaham and Stewart, 1995;Fattore et al, 2003;Leri et al, 2004;Luo et al, 2004;Yao et al, 2005) whereas in the present study, no programmed responsecontingent cues were available during reinstatement testing. As drugs of abuse can dramatically increase responding for both unconditioned and conditioned sensory stimuli in drug-naïve animals (eg, Berlyne, 1969;Gomer and Jakubczak, 1974;Robbins, 1976;Robbins and Koob, 1978), this factor could also have contributed to the specific outcome of the present study.…”
Section: Discussionmentioning
confidence: 74%
“…To this aim, the acquisition, maintenance and extinction of cocaine self-administration (SA) behavior was assessed in RHA and RLA rats using a continuous (FR-1) reinforcement schedule with lever-pressing as operandum. Next, the propensity of RHA and RLA rats, kept under extinction conditions for 3 weeks, to resume lever-pressing behavior upon the administration of priming doses of cocaine was investigated by means of a between-session model of extinction/reinstatement, as previously described (Fattore et al, 2003). Finally, cocaine was made again contingently available to compare the ability of the two lines to reacquire SA behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory animal study has shown that the reinforcing and motivational effects of heroin and heroin-paired stimuli are mediated, at least in part, by activation of cannabinoid CB1 receptors (De Vries et al, 2003).Drugs antagonizing the cannabinoid receptors to modulate DA cells but also postsynaptic responses from DA stimulation (Wallmichrath and Szabo, 2002;Julian et al, 2003) have shown promising results in attenuating the reinforcing effects of various types of drugs of abuse in laboratory animals (De Vries et al, 2001). As far as heroin is concerned, there are findings indicating that relapse to heroin after an extended drug-free period is triggered by cannabinoid agonists and that cannabinoid antagonist can prevent drug-seeking behaviors (Fattore et al, 2003).…”
Section: Da and Heroin Addiction Treatment Implicationsmentioning
confidence: 99%